Fundamentals of the Study of Urine and Body Fluids - Ridley, John W. (Springer International Publishing, 2018)
This volume provides the essential theory as well as practice for the study of urine samples and body fluids other than urine. It is a concise compendium of information of a practical nature while additionally serving as a clinical resource leading to an understanding of clinical conditions for patients whose test specimens indicate the presence of a pathological condition. Selective laboratory procedures inform the investigator not only of how specimens are processed, but also the rationale for performing specific examinations. Parameters by which testing personnel may measure or evaluate the validity, accuracy and clinical implications of test results for clinical importance providing optimum and useful information are provided.